Multidisciplinary Treatment Approach in a Patient with History of Nasopharyngeal Carcinoma - DOĞAN, BAŞAK; TÜRKAYDIN, DİLEK; AĞRALI, ÖMER BİRKAN (My University, 2014)
Radiotherapy in NPC patients has side effects on the dentition, which affects quality of life dramatically. This case report presents multidisciplinary dental treatment approach in a 17-year-old male patient with a history of nasopharyngeal carcinoma (NPC), which was treated with chemotherapy and radiotherapy. The adolescent patient applied to dental hospital 4 years after the radiotherapy with aesthetic and functional problems on dentition affecting psychological, social, and physical aspects of his life. The dentition of the patient demonstrated the severe destruction as a devastating side effect of radiotherapy. With a successful multidisciplinary approach, our patient's aesthetics, function, and self-confidence were obtained. Well-established procedures, which include preventative care and maintenance, can reduce the duration and expenses of the treatment and help in challenging the life-long complications of radiotherapy.